2012
DOI: 10.1159/000338096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postnatal Intermittent Hypoxia on Growth and Cardiovascular Regulation of Rat Pups

Abstract: Background: Intermittent hypoxic episodes are common among preterm infants, although longer term consequences on growth pattern and cardiovascular regulation are unclear. Furthermore, the effects of intermittent hypoxia (IH) may depend on the pattern of hypoxia-reoxygenation. Objectives: We tested the hypothesis that a clustered versus dispersed pattern of repetitive IH during early postnatal life would induce differential long-term alteration in growth and cardiovascular regulation. Methods: Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
(31 reference statements)
6
22
0
Order By: Relevance
“…It has also been noted that prior to IH-exposed rats reaching maturity, weight gain is not parallel between IH-and non-IH-exposed groups and after reaching maturity, both groups reach similar body weights due to growth catch-up (8,26). This study found similar body weights between treatment and control groups at 100 days of age, reinforcing this previously documented body weight phenomenon.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has also been noted that prior to IH-exposed rats reaching maturity, weight gain is not parallel between IH-and non-IH-exposed groups and after reaching maturity, both groups reach similar body weights due to growth catch-up (8,26). This study found similar body weights between treatment and control groups at 100 days of age, reinforcing this previously documented body weight phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…Neonatal IH has previously been associated with a decreased growth rate during the neonatal period (8,10,26). It has also been noted that prior to IH-exposed rats reaching maturity, weight gain is not parallel between IH-and non-IH-exposed groups and after reaching maturity, both groups reach similar body weights due to growth catch-up (8,26).…”
Section: Discussionmentioning
confidence: 99%
“…They are typically a consequence of impaired respiratory control and may occur in spontaneously breathing or ventilated preterm infants 3, 19, 20 . Intermittent hypoxia and/or related apnea events during early postnatal life have been linked to neurodevelopmental impairment 21, 22, 23, 24 , attention deficit disorder 25 , neurotransmitter imbalance 25 , retinopathy of prematurity 3, 26 , cardiovascular regulation 27 and growth restriction 27 in both human infants and neonatal animal models. We are only beginning to appreciate that patterns of IH may play a role in both detrimental and beneficial effects on the respiratory, cardiovascular, and nervous systems among others 26, 28 .…”
Section: Discussionmentioning
confidence: 99%
“…IH effects on cardiovascular control are more complex and longer lasting. Changes in arterial blood pressure are dependent on the timing of the IH events with a clustered pattern associated with lower blood pressure than equaling dispersed events 40 with no recovery in either IH paradigm after 7 weeks of exposure. Interestingly, there is an association between extreme prematurity, increased blood pressure in adolescence and functional vascular changes, although it is speculative whether intermittent hypoxic episodes in early life might be contributory 41 .…”
Section: Consequences Of Intermittent Hypoxic Episodesmentioning
confidence: 98%
“…In rodent models, IH exposure during early postnatal life restricts both body 40 and brain growth 19 , however, these effects were reversed after a few weeks of recovery. IH effects on cardiovascular control are more complex and longer lasting.…”
Section: Consequences Of Intermittent Hypoxic Episodesmentioning
confidence: 99%